2014
DOI: 10.1074/jbc.m113.539452
|View full text |Cite
|
Sign up to set email alerts
|

The Circulating Glycosaminoglycan Signature of Respiratory Failure in Critically Ill Adults

Abstract: Background: Endothelial glycocalyx degradation contributes to the pathogenesis of critical illness. Results: Mechanically ventilated subjects exhibited plasma glycocalyx breakdown signatures (glycosaminoglycan fragments) characteristic of direct versus indirect etiologies of respiratory failure. Conclusion: Circulating glycosaminoglycans provide insight into respiratory failure pathophysiology. Significance: This is the first study to characterize circulating glycosaminoglycans during critical illness, offerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(158 citation statements)
references
References 36 publications
14
138
2
4
Order By: Relevance
“…In contrast to the present fi ndings, Ware et al 22,23 reported in two separate studies that plasma vWF levels were signifi cantly lower at baseline in subjects with indirect ARDS than in subjects with direct ARDS, although discrepancies in severity of illness may have been responsible for this diff erence in at least one of the studies. In a novel recent report, Schmidt et al 24 reported diff erent circulating glycosaminoglycan patterns (likely refl ecting degradation of the endothelial glycocalyx) in patients with direct vs indirect lung injury. However, to our knowledge, the current study is the fi rst to test a multipathway panel of biomarkers in two separate cohorts of patients with direct vs indirect ARDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the present fi ndings, Ware et al 22,23 reported in two separate studies that plasma vWF levels were signifi cantly lower at baseline in subjects with indirect ARDS than in subjects with direct ARDS, although discrepancies in severity of illness may have been responsible for this diff erence in at least one of the studies. In a novel recent report, Schmidt et al 24 reported diff erent circulating glycosaminoglycan patterns (likely refl ecting degradation of the endothelial glycocalyx) in patients with direct vs indirect lung injury. However, to our knowledge, the current study is the fi rst to test a multipathway panel of biomarkers in two separate cohorts of patients with direct vs indirect ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…First, not all biomarkers previously associated with ARDS pathogenesis or prognosis were measured. Other biomarkers associated with lung epithelial cell injury (club cell 16, KL-6), 34,35 endothelial injury (soluble intercellular adhesion molecule-1, circulating glycosaminoglycans), 24,30 disordered coagulation and fi brinolysis (plasminogen activator inhibitor-1, protein C, thrombomodulin), 36,37 and infl ammation (IL-1/IL-1-receptor antagonist, soluble tumor necrosis factor receptor 1), 38 to name a few, might further enhance the molecular phenotypes of epithelial and endothelial injury in direct vs indirect ARDS. Second, the larger of the two patient samples used in these analyses came from a secondary analysis of a randomized controlled trial, which excluded many patients at highest risk for mortality from ARDS and was not designed to test the hypothesis under study in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proposed inflammation-induced shedding of glycocalyx associated with endothelial dysfunction in inflammatory cascade [5][6][7][8]. Furthermore, recent clinical studies reported the elevation of glycocalyx constitution in the blood plasma and urine of human patients with sepsis, suggesting that the circulating glycocalyx fragment might be derived from the destruction of vascular ESL [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…d Direct lung injury: in contrast to indirect/systemic lung injury, direct lung injury arises from insults that primarily target the lung epithelium. Accordingly, patients with pneumonia-induced respiratory failure have less circulating HS than patients with sepsis-or pancreatitisinduced respiratory failure (45). These differences may reflect insult-dependent roles of heparanase in lung injury: although heparanase knockout mice were protected from polymicrobial sepsis-induced lung injury (16), no such protection was enjoyed after intranasal LPS (46).…”
Section: Acute Lung Injurymentioning
confidence: 84%